Oxylipin secretion by human CD3+ T lymphocytes in vitro is modified by the exogenous essential fatty acid ratio and life stage - von Gerichten, Johanna; West, Annette L.; Irvine, Nicola A.; Miles, Elizabeth A.; Calder, Philip C.; Lillycrop, Karen A.; Burdge, Graham C.; Fielding, Barbara A. (Frontiers in Immunology, 2023)
Immune function changes across the life stages; for example, senior adults exhibit a tendency towards a weaker cell-mediated immune response and a stronger inflammatory response than younger adults. This might be partly mediated by changes in oxylipin synthesis across the life course. Oxylipins are oxidation products of polyunsaturated fatty acids (PUFAs) that modulate immune function and inflammation. A number of PUFAs are precursors to oxylipins, including the essential fatty acids (EFAs) linoleic acid (LA) and α-linolenic acid (ALA). LA and ALA are also substrates for synthesis of longer chain PUFAs. Studies with stable isotopes have shown that the relative amounts of LA and ALA can influence their partitioning by T lymphocytes between conversion to longer chain PUFAs and to oxylipins. It is not known whether the relative availability of EFA substrates influences the overall pattern of oxylipin secretion by human T cells or if this changes across the life stages. To address this, the oxylipin profile was determined in supernatants from resting and mitogen activated human CD3+ T cell cultures incubated in medium containing an EFA ratio of either 5:1 or 8:1 (LA:ALA). Furthermore, oxylipin profiles in supernatants of T cells from three life stages, namely fetal (derived from umbilical cord blood), adults and seniors, treated with the 5:1 EFA ratio were determined. The extracellular oxylipin profiles were affected more by the EFA ratio than mitogen stimulation such that n-3 PUFA-derived oxylipin concentrations were higher with the 5:1 EFA ratio than the 8:1 ratio, possibly due to PUFA precursor competition for lipoxygenases. 47 oxylipin species were measured in all cell culture supernatants. Extracellular oxylipin concentrations were generally higher for fetal T cells than for T cells from adult and senior donors, although the composition of oxylipins was similar across the life stages. The contribution of oxylipins towards an immunological phenotype might be due to the capacity of T cells to synthesise oxylipins rather than the nature of the oxylipins produced.